PERBEDAAN KADAR SGPT PADA PASIEN TUBERKULOSIS PARU SEBELUM DAN SESUDAH FASE INTENSIF DI POLIKLINIK PARU RSUD ARIFIN ACHMAD PEKANBARU - Rafika Annisa; Zarfiardy Aksa Fauzi; Fridayenti " (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTTuberculosis (TB) is still a cause of high morbidity which can mainly due to the onset of side effects from the use of Anti-Tuberculosis Drugs (OAT). One of the most serious side effects are hepatotoxic. Early markers of hepatotoxicity is an increase of enzymes in serum transaminase consisting of glutamate oxaloacetate transaminase (SGOT) which is secreted in parallel with glutamate pyruvate transaminase (SGPT). This study aims to determine differences in SGPT levels before and after intensive phase in patients with pulmonary tuberculosis in the pulmonary polyclinic of Arifin Achmad general hospital Pekanbaru. This research uses descriptive method with cross sectional approach. The sampling technique used is total sampling technique. The study was conducted in February-May 2015 and obtained 32 samples which is a tuberculosis patient at the Pulmonary Polyclinic Arifin Achmad general hospital. Results from this study are characteristic of most patients by age is 18-54 years is 22 (68.8%) of people, sex is a male majority, with result 19 (59.4%) people. SGPT levels of pulmonary tuberculosis patients after intensive phase for 8 weeks found elevated levels of ALT in 1 (3.1%). Based on an analysis using paired sample t test found a significant difference between the levels of ALT before and after the 8-week intensive phase during which p = 0.001 <0.005.Keywords: Pulmonary tuberculosis, SGPT levels.